INCIDENCE OF PSP IN PREVIOUSLY DIAGNOSED PARKINSON DISEASE PATIENTS (The Research of Medical Science Review, 2025)
Objective: To observe the incidence of PSP in previously diagnosed Parkinson Disease PatientsStudy Design: A Descriptive Case SeriesStudy Duration: 06 months Study Place: Tertiary Care Hospital, LahoreMethods: A sample size of 110 was calculated using WHO calculator. Demographic data was taken. Patients were enrolled as per inclusion criteria. Detailed general physical and systemic examination was done. Patients were looked for the signs of the PSP and also detailed history about medication used and previous comorbids was also taken. The NINDS-SPSP was applied to diagnose PSP> All of these patients were those who had been previously diagnosed with Parkinson Disease. Data was analysed in SPPS version 23.Results: Total 110 patients were enrolled in our studies, among them 81 were males and 29 were females. The average onset of symptoms was 72±3 years. The most common symptom in our study was rigidity of trunk and knee muscles (94.5%), frontal cognitive defect which was evident in 93.6%, and then followed by downward gaze impairment (88.1%). Other symptoms include neck dystonia, convergence defects, apathy, disinhibition, frequent falls and difficulty falling asleep. Males were effected more in our study, with males effected thrice more than females.Conclusion: PSP is a rare disease and it relies on clinical diagnosis. The chances of a patient being diagnosed with Parkinson Disease is quite high, however detailed history and thorough examination is what required diagnosing patient with PSP.